Regulatory T cells and macrophages in atherosclerosis: from mechanisms to clinical significance - Ouyang, Xin (Frontiers in Immunology, 2024)
Atherosclerosis is a complex pathological process, which causes diseases that threaten the health of an increasing number of people. Studies have found that the original view of lipid accumulation is not comprehensive because the use of lipid-lowering drugs alone cannot effectively treat atherosclerosis. As the study of the pathogenesis of atherosclerosis develops in-depth, the impact of immune-inflammatory response on atherosclerosis has garnered a great deal of attention. Some new advances have been made in the role of regulatory T cells (Tregs) and macrophages with unique immunomodulatory functions in atherosclerosis. Herein, the role of Tregs, macrophages, the mechanisms of Tregs-regulated macrophages, and the effects of potential factors on Tregs and macrophages in atherosclerosis are overviewed. Targeting Tregs and macrophages may provide new research strategies for the treatment of atherosclerosis in the clinic.